Aid Effectiveness in Times of Political Change: Lessons from the Post-Communist Transition - Anders Olofsgård; Maria Perrotta Berlin; Emmanuel Frot (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2013)
We argue that the tilt towards donor interests over recipient needs in aid allocation and practices may be particularly strong in new partnerships. Using the natural experiment of Eastern transition we find that commercial and strategic concerns influenced both aid flows and entry in the first half of the 1990s, but much less so later on. We also find that fractionalization increased and that early aid to the region was particularly volatile, unpredictable and tied. Our results may explain why aid to Iraq and Afghanistan has had little development impact and serve as warning for Burma and Arab Spring regimes.
Keywords: F35; F63; 330; foreign aid; development